Does loud noise affect the clinical decision-making processes of healthcare professionals in a simulated emergency setting? - Folscher, Lindy-Lee (My University, 2013)
Introduction: Healthcare professionals working in the Emergency Medicine field are often required to function in difficult environments. Noise is one environmental factor that may adversely affect their performance. Objectives: To firstly determine if there is any difference in cognitive task performance required for clinical decision-making of healthcare professionals in a quiet compared to a noisy environment and secondly, to assess the subjective experience of participants with regards to performance in a noisy environment. Design: Prospective cross-over study. Setting: Three Academic Hospitals in Johannesburg. Participants: Forty one doctors exposed to emergency management of patients. Methods: A 30 minute examination consisting of six matched and pre-validated questions was conducted. Half of the questions were completed with exposure to ambient noise (range 40-45dB(A)) and the other half with exposure to pre-recorded background Emergency Department noise at 80-85dB(A). The questions were completed in alternating quiet and noise. Each question was scored out of 10 and the time taken to complete each question was recorded. Main Results: Overall mean test scores in quiet and noise were 18.7/30 and 19.4/30 (p=0.36) respectively, with overall time for test completion of 836s in quiet and 797s (p=0.005) in noise. While there was no statistically significant difference in task performance, 65% of the doctors found the noise distracting with 88% experiencing varying degrees of stress. Conclusions: This study showed no difference in cognitive performance in a quiet compared to a noisy environment. Deterioration in functionality might be seen with higher levels of noise and/or longer exposure.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Emergency Medicine. Johannesburg, 2012
Keywords: Noise; Noise, Occupational; Emergency Service, Hospital